Pengaruh Pendapatan, Tingkat Pendidikan, Dan Akses Media Informasi Terhadap Minat Masyarakat Muslim Dalam Berwakaf Uang Di Kota Jakarta Timur - Hasan, Nurul Ichsan; Deti Aliawati; Ady Cahyadi (FEB Universitas Muhammadiyah Jakarta, 2025)
This study aims to determine the effect of income, level education, and media access to information on the interest of Muslim communities in Cash Waqf in the city of East Jakarta. The data used are primary data using a questionnaire technique thas was distributed to 100 Muslim community respondents who have income and interest in Cash Waqf. The number of variables studied were 4 variables, namely incom, education level, and access to information media as an independen variable and the variable of interest in terms of Cash Waqf as the dependent variable. The approach used in this research is a quantitative approach. The sampling method used is nonprobability sampling with a sampling technique that is accidental sampling in Muslim communities in the city of East Jakarta who have interest/desire to represent Cash Waqf, both endowments and non-endowments. Analytical methods wirh descriptive statistics and inferential statistics and multiple linear regression analysisi with SPSS 16.0 and Microsoft Excel 2010 to test the hypotheses of the variables used. The result of this study indicate that the variables of income, level of education, and access to information media have a significant effect on interest in Cash Wawf with a significance value of 0,000 less than the alpha value of 0,05 or 5%. Partially the income variable, education level, and media access to information also have a significant influence on the interest of Cash Waqf. The predictive ability of the three independent variables on the dependent variable is 58%. Whille the remaining 42% is influenced by other factors not included in this research variable. Keyword : Income, Level of education, Access to Media Information, Interes in representing Cash Waqf